Podcasts impact on the listening skill development in a private school in a Latin American country - Molina, Lourdes; Arteaga, Magali (Indonesian Journal of Education and Pedagogy, 2024)
Podcasts are digital tools, which consist in audio files that can be downloaded from any technological devices connected to internet. There is some research that support the use of this tool in the processo of EFL classes, but there is a research gap in the field in our country. For this reason, this research analyzed the effectiveness of the use of podcasts as a didactic tool to improve the listening comprehension skill in English in eighth grade students. A population of 72 students was evaluated through a pre-test and post-test. This is a quasi-experimental design with quantitative data. Satistical analyses were used to measure the impact of the intervention. The Mass Whitney test was applied due to the lack of normality in the data. The results of the Mann Whitney U test revealed a significant difference in the development of the skill after the implementation. Likewise, the paired t-test results demonstrated a relevant variation in the English listening comprehension skills before and after the implementation of the podcast, with a p value less than the significance level of 0.05. The research findings suggest that the use of podcasts as a teaching tool is effective in improving listening comprehension skills. The results open the door for implications aimed at the use of podcasts in English classes to help students reach proficiency in the language.